An Analysis of the Competitive Strategy of PT Gunanusa Eramandiri in the Crunchy Peanut Industry in Indonesia - , Nur Aini Fitriya Ardiani Aniqoh; , Dr. Bambang Riyanto LS, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research objectives are: 1) to evaluate the strategy of PT Gunanusa Eramandiri